Microbial-Driven Immunological Memory and Its Potential Role in Microbiome Editing for the Prevention of Colorectal Cancer - Campillo-Gimenez, Laure; Rios-Covian, David; Rivera-Nieves, Jesus; Kiyono, Hiroshi; Chu, Hiutung; Ernst, Peter B. (Frontiers in Cellular and Infection Microbiology, 2021)
Over the last several years, many advances have been made in understanding the role of bacteria in the pathogenesis of gastrointestinal cancers. Beginning with Helicobacter pylori being recognized as the first bacterial carcinogen and the causative agent of most gastric cancers, more recent studies have examined the role of enteric microbes in colorectal cancer. In the digestive tract, these communities are numerous and have a complex interrelationship with local immune/inflammatory responses that impact the health of the host. As modifying the microbiome in the stomach has decreased the risk of gastric cancer, modifying the distal microbiome may decrease the risk of colorectal cancers. To date, very few studies have considered the notion that mucosal lymphocyte-dependent immune memory may confound attempts to change the microbial components in these communities. The goal of this review is to consider some of the factors impacting host-microbial interactions that affect colorectal cancer and raise questions about how immune memory responses to the local microbial consortium affect any attempt to modify the composition of the intestinal microbiome.